Design and Application of 3-Alkyl-2-vinylindoles in Brønsted Acid Catalyzed Reactions - Mei, Guang-Jian; Shi, Feng (Synlett, 2016)
Our group has designed and developed 3-alkyl-2-vinylindoles as a new type of vinylindoles, which have displayed versatile reactivity in Brønsted acid catalyzed reactions. For instance, this class of vinylindoles can act as 2C building blocks in [n+2] cyclizations, as 2,3-disubstituted indoles in dearomatizations, and as NCC building blocks in [3+2] cyclodimerizations. This article summarizes the main contributions of our group in this research field.1 Introduction2 As 2C building blocks in [n+2] cyclizations3 As 2,3-disubstituted indoles in dearomatization4 As NCC building blocks in [3+2] cyclodimerizations5 Summary and outlook
Keywords: vinylindole; cyclization; dearomatization; chiral phosphoric acid; organocatalysis